Genitofemoral and Perineal Neuralgia After Transobturator Midurethral Sling - Parnell, Brent A. (Obstet Gynecol, 2012)
BACKGROUND: Midurethral slings successfully treat stress urinary incontinence through a minimally invasive vaginal approach. Postoperative pain related to sling placement can occur and poses both diagnostic and treatment dilemmas. CASE: Four years after transobturator midurethral sling placement, the patient presented with complaints of left labial pain and dyspareunia since surgery. Using sensory mapping and a nerve stimulator, the problem was identified in the distribution of the genitofemoral nerve. Conservative therapy with a centrally acting neuromodulatory drug and nerve block relieved the pain. CONCLUSION: Postsling neuralgia diagnosis using sensory mapping and a nerve stimulator aids in indentifying the nerve involved and in successful conservative treatment with a nerve block.